Simple rules how to thrive in a complex world - Sull, Donald N. ca. 20. Jh; Eisenhardt, Kathleen M. 1947- (Mariner Books, 2016)
"How simplicity trumps complexity in nature, business, and life. We struggle to manage complexity every day. We follow intricate diets to lose weight, juggle multiple remotes to operate our home entertainment systems, face proliferating data at the office, and hack through thickets of regulation at tax time. But complexity isn't destiny. Sull and Eisenhardt argue there's a better way: By developing a few simple yet effective rules, you can tackle even the most complex problems. Simple rules are a hands-on tool to achieve some of our most pressing personal and professional objectives, from overcoming insomnia to becoming a better manager or a smarter investor. Simple rules can help solve some of our most urgent social challenges from setting interest rates at the Federal Reserve to protecting endangered marine wildlife along California's coast. Drawing on more than a decade of rigorous research, the authors provide a clear framework for developing effective rules and making them better over time. They find insights in unexpected places, from the way Tina Fey codified her experience working at Saturday Night Live into rules for producing 30 Rock (rule five: never tell a crazy person he's crazy) to burglars' rules to choose a house to rob ("avoid houses with a car parked outside") to Japanese engineers using the foraging rules of slime molds to optimize Tokyo's rail system. Whether you're struggling with information overload, pursuing opportunities with limited resources, or just trying to change your bad habits, Simple Rules provides a powerful way to tame complexity. "..
Keywords: BUSINESS & ECONOMICS / Decision-Making & Problem Solving; BUSINESS & ECONOMICS / Statistics; SELF-HELP / Personal Growth / Success; Statistik; Wirtschaft; Simplicity; Conduct of life; Decision making; Erfolg; Entscheidungsfindung; Lebensführung; Heuristik; Entscheidungsregel